P221 Drug and alcohol misuse is associated with STIS in men who have sex with men (MSM). (18th May 2015) - Rawdah, Waseem; Mulka, Larissa; Youssef, Elaney; Tooke, Ben; Richardson, Daniel
Abstract : Background/introduction: Alcohol and recreational drug misuse is an increasing problem in sexual health clinics, particularly MSM where it is often associated with unsafe sexual practices and increasing prevalence of sexually transmitted infections (STIs). Aims/objectives: To determine the proportion of MSM testing positive for STIs reporting substance misuse in a dedicated sexual health clinic, compared to the proportion attending THT services reporting high risk sexual activity requiring support for substance misuse. Methods: Case notes of patients attending a MSM clinic testing positive for STIs over a 6 month period were reviewed. Data was collected on type of STI, recreational drug and alcohol use. Over the same period, data on high-risk sexual activity and referral to specialist drug and alcohol services was collected for MSM attending THT services. Results: 285 MSM attended the sexual health clinic, whereby 97 (34%) tested positive for 1 or more STI. 88 cases of gonorrhoea were seen, 49 cases of chlamydia, 20 cases of syphilis and 7 new HIV infections. Of those testing positive for STIs, 45 (46%) reported alcohol and/or recreational drug misuse. Of the 162 MSM attending THT services, 90 (56%) reported high risk sexual behaviour with concurrent substance misuse. 27 (30%) were referred to specialist substance misuse services. Discussion/conclusions: High rates of substance misuse associated with high risk sexual activity were seen in the MSM clinic and at THT. This reinforces the importance of screening and brief intervention/referral for substance misuse as a risk reduction strategy for STIs and HIV.